HLA‐A*33‐DR3 and A*33‐DR9 haplotypes enhance the risk of type 1 diabetes in Han Chinese. Issue 4 (3rd May 2016) - Zhang, Juanjuan; Zhao, Liebin; Wang, Bokai; Gao, Jie; Wang, Li; Li, Li; Cui, Bin; Hu, Min; Hong, Jie; Gu, Weiqiong; Wang, Weiqing; Ning, Guang
Abstract: Aims/Introduction: To investigate the typing for human leukocyte antigen ( HLA ) class I in Chinese patients with type 1 diabetes as a complement screening for HLA class II. Materials and Methods: A total of 212 type 1 diabetic patients and 200 healthy controls were enrolled. The genetic polymorphisms of HLA class I and II were examined with a high‐resolution polymerase chain reaction sequence‐based typing method. Results: The haplotype, A*33:03‐B*58:01‐C*03:02(A33), was associated with type 1 diabetes ( P = 1.0 × 10 −4, odds ratio 3.2 [1.738–5.843]). The A33‐DR3 and A33‐DR9 haplotypes significantly enhanced the risk of type 1 diabetes (A33‐ DR3, odds ratio 5.1 [2.40–10.78], P = 4.0 × 10 −6 ; A33‐ DR9, odds ratio 13.0 [1.69–100.32], P = 0.004). In type 1 diabetic patients, compared with A33‐DR3 ‐negative carriers, A33‐DR3 ‐positive carriers had significantly lower percentages of CD3 + CD4 + T cells (42.5 ± 7.72 vs 37.0 ± 8.35%, P = 0.023), higher percentages of CD3 + CD8 + T cells (27.4 ± 7.09 vs 32.8 ± 5.98%, P = 0.005) and T‐cell receptor α/β T cells (70.0 ± 7.00 vs 73.6 ± 6.25%, P = 0.031), and lower CD4/CD8 ratios (1.71 ± 0.75 vs 1.16 ± 0.35, P = 0.003). Conclusions: It is the first time that the haplotypes A33‐DR3 and A33‐DR9 were found with an enhanced predisposition to type 1 diabetes in Han Chinese. A33‐DR3 was associated with a reduction in the helper‐to‐cytotoxic cell ratio and preferential increase of T‐cell receptor α/β T cell. The typing for HLA class I and its immunogenetic effects are important for more accurate HLA class II haplotype risk prediction and etiology research in type 1 diabetic patients. Abstract : The HLA‐A*33‐DR3 and A*33‐DR9 Haplotypes Enhance the Risk of Type 1 Diabetes in Han Chinese.